Zingiber inodorum (Zingiberaceae: Zingiberoideae), a new species of Z. sect. Cryptanthium from Hainan, China - Wang, Qing-Long; Yuan, Lang-Xing; Tang, Huan; Bai, Lin (Phytotaxa, 2024)
Zingiber inodorum, a new species belonging to Z. sect. Cryptanthium from Hainan, China, is described and colour plates showing its distinctive features are provided. Information on its distribution, ecology and phenology is also provided and a preliminary IUCN conservation assessment of the species is proposed. An unpublished phylogenetic study shows that Z. inodorum is related to a group of 11 species that is informally named as “Zingiber cochleariforme group”. A key to these species is provided. Among them, Z. inodorum is mostly similar to Z. guangxiense from south and southeast China in its inflorescence and flower characters. Zingiber inodorum is also similar to Z. magang and Z. skornickovae from central Vietnam in its vegetative characters. A tabulated comparison of Z. inodorum, Z. guangxiense, Z. magang and Z. skornickovae is provided.